Reworking race : the making of Hawaii's interracial labor movement - Jung, Moon-Kie (Columbia University Press, 2006)
In the middle decades of the twentieth century, Hawai'i changed rapidly from a conservative oligarchy firmly controlled by a Euro-American elite to arguably the most progressive part of the United States. Spearheading the shift, tens of thousands of sugar, pineapple, and longshore workers eagerly joined the left-led International Longshoremen's and Warehousemen's Union (ILWU) and challenged their powerful employers. In this theoretically innovative study, Moon-Kie Jung explains how Filipinos, Japanese, Portuguese, and others overcame entrenched racial divisions and successfully m.